2017
DOI: 10.1002/jso.24885
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal dysfunction after laparoscopic low anterior rectal resection for rectal cancer with and without radiotherapy (manometry study)

Abstract: RT significantly deteriorates the functional outcome of patients after LAR. Manometry revealed internal sphincter dysfunction, reduced capacity, and compliance of neorectum, which seem to have a significant correlation with LARS presence/seriousness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 34 publications
2
35
1
3
Order By: Relevance
“…Therefore, the need to evaluate LARS score occurs—several randomized controlled trials have demonstrated an almost 2-fold higher LARS prevalence in patients undergoing chemoradiotherapy with surgery compared to surgery alone ( 27 , 28 ). In a recent study by Ihnát et al ., authors compared LARS score following the surgery with or without radiotherapy and found that in the surgery alone group, 14.8% of the patients had major LARS and 37.0% of the patients had minor LARS compared to surgery plus radiotherapy group−53.6% of the patients with major LARS and 31.6% of the patients with minor LARS ( 29 ). In this study, the effect of chemoradiotherapy was not investigated, which could be added in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the need to evaluate LARS score occurs—several randomized controlled trials have demonstrated an almost 2-fold higher LARS prevalence in patients undergoing chemoradiotherapy with surgery compared to surgery alone ( 27 , 28 ). In a recent study by Ihnát et al ., authors compared LARS score following the surgery with or without radiotherapy and found that in the surgery alone group, 14.8% of the patients had major LARS and 37.0% of the patients had minor LARS compared to surgery plus radiotherapy group−53.6% of the patients with major LARS and 31.6% of the patients with minor LARS ( 29 ). In this study, the effect of chemoradiotherapy was not investigated, which could be added in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative radiotherapy also causes deterioration of anal sphincter function [ 44 , 45 ]. The effect of radiotherapy is not only clinically significant, but also is visible in manometric studies [ 46 ]. Nevertheless, radiotherapy significantly improves overall survival and disease-free survival, and thus the elimination of this part of modern treatment is not possible [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anorectal manometry may be useful [17,47,48] not as a diagnostic tool but to guide biofeedback therapy. It may help to quantify anal sphincter contraction and determine whether duration and/or amplitude should be targeted by the biofeedback.…”
Section: Section Iv: Recommended Work‐upmentioning
confidence: 99%